GSTM1 and APE1 genotypes affect arsenic-induced oxidative stress: a repeated measures study - Quamruzzaman Quazi; Hoffman Elaine; Catalano Paul J; Kile Molly L; Breton Carrie V; Rahman Mahmuder; Mahiuddin Golam; Christiani David C (BMC, 2007)
Abstract Background Chronic arsenic exposure is associated with an increased risk of skin, bladder and lung cancers. Generation of oxidative stress may contribute to arsenic carcinogenesis. Methods To investigate the association between arsenic exposure and oxidative stress, urinary 8-hydroxy-2'-deoxyguanosine (8-OHdG) was evaluated in a cohort of 97 women recruited from an arsenic-endemic region of Bangladesh in 2003. Arsenic exposure was measured in urine, toenails, and drinking water. Drinking water and urine samples were collected on three consecutive days. Susceptibility to oxidative stress was evaluated by genotyping relevant polymorphisms in glutathione-s transferase mu (GSTM1), human 8-oxoguanine glycosylase (hOGG1) and apurinic/apyrimidinic endonuclease (APE1) genes using the Taqman method. Data were analyzed using random effects Tobit regression to account for repeated measures and 8-OHdG values below the detection limit. Results A consistent negative effect for APE1 was observed across water, toenail and urinary arsenic models. APE1 148 glu/glu + asp/glu genotype was associated with a decrease in logged 8-OHdG of 0.40 (95%CI -0.73, -0.07) compared to APE1 148 asp/asp. An association between total urinary arsenic and 8-OHdG was observed among women with the GSTM1 null genotype but not in women with GSTM1 positive. Among women with GSTM1 null, a comparison of the second, third, and fourth quartiles of total urinary arsenic to the first quartile resulted in a 0.84 increase (95% CI 0.27, 1.42), a 0.98 increase (95% CI 033, 1.66) and a 0.85 increase (95% CI 0.27, 1.44) in logged 8-OHdG, respectively. No effects between 8-OHdG and toenail arsenic or drinking water arsenic were observed. Conclusion These results suggest the APE1 variant genotype decreases repair of 8-OHdG and that arsenic exposure is associated with oxidative stress in women who lack a functional GSTM1 detoxification enzyme.